2020
DOI: 10.1523/jneurosci.1525-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Serine Racemase Regulates NMDA Receptor Function

Abstract: for their assistance in mouse breeding and genotyping. Human tissue was obtained from the NIH NeuroBioBank. Competing Interests: JTC reports consulting with Concert Pharm and holding a patent on D-serine for the treatment of serious mental illness, which is owned by Massachusetts General Hospital. DTB served as a consultant for LifeSci Capital and received research support from Takeda Pharmaceuticals. All other authors declare no competing financial interests.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 74 publications
5
23
0
Order By: Relevance
“…More recent studies, using the SRKO mice as controls, have (53,(77)(78)(79)(80)(81)(82)(83)(84). Furthermore, in agreement with previous studies in cultured neurons (85,86), we recently reported that SR localizes to the apical dendrites and the post-synaptic density in situ in hippocampal CA1 pyramidal neurons and regulates postsynaptic NMDARs (64). Importantly, while conditional knockout (cKO) of SR from astrocytes has minimal impact on SR levels, cKO from CaMKIIa-expressing forebrain glutamatergic neurons results in $65% reduction of SR expression in the cortex and hippocampus (59).…”
Section: Deletion Of Sr From Ca1 Pyramidal Neurons Results In a Cell-autonomous Reduction In Gabaergic Synapsessupporting
confidence: 90%
See 2 more Smart Citations
“…More recent studies, using the SRKO mice as controls, have (53,(77)(78)(79)(80)(81)(82)(83)(84). Furthermore, in agreement with previous studies in cultured neurons (85,86), we recently reported that SR localizes to the apical dendrites and the post-synaptic density in situ in hippocampal CA1 pyramidal neurons and regulates postsynaptic NMDARs (64). Importantly, while conditional knockout (cKO) of SR from astrocytes has minimal impact on SR levels, cKO from CaMKIIa-expressing forebrain glutamatergic neurons results in $65% reduction of SR expression in the cortex and hippocampus (59).…”
Section: Deletion Of Sr From Ca1 Pyramidal Neurons Results In a Cell-autonomous Reduction In Gabaergic Synapsessupporting
confidence: 90%
“…The lack of apparent seizure activity with the increase E/I ratio further suggests concurrent homeostatic processes, though we cannot rule out covert temporal lobe epileptiform bursting in the SRKO mice. Furthermore, other compensatory mechanisms could contribute to the normalization of LTP in the SRKO mice, including an increase in hippocampal glycine levels (109), and an increased in synaptic GluN2B (53,64). Overall, these homeostatic changes suggest that there is a prioritization of synaptic and cellular functions over network function resulting in a disruption of the signalto-noise ratio and impairing cognition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation of increased synaptic enrichment of NMDARs relative to WT within the hippocampus is expected based on previous studies on SRKO mice showing increased expression of GluN1 (37,38) and GluN2B (23,51). These changes in the overall number and composition of NMDARs are likely to be the consequence of lack of D-serine, as prior studies have demonstrated the role of co-agonist binding in priming of the NMDAR for endocytosis, with D-serine specifically acting on GluN2B subunits (52,53).…”
Section: Discussionsupporting
confidence: 81%
“…For example, there is an apparent discrepancy regarding changes in synaptic plasticity and NMDAR activation at CA3/CA1 hippocampal synapses. On one hand, studies of isolated excitatory glutamate transmission on CA1 pyramidal cells reported LTP deficits and altered NMDAR activation in slices from SR-KO mice [ 23 , 26 , 27 ]. On the other hand, extracellular recordings that monitor the overall network activity did not show differences in LTP [ 10 , 28 ].…”
Section: Introductionmentioning
confidence: 99%